Melawan Kekuasaan Laki-Laki: Kajian Feminis Eksistensialis “Perempuan di Titik Nol” Karya Nawal el-Saadawi - Mulyo Hadi Purnomo (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Women's resistance to male power is increasingly voiced in various media. This is a form of increased awareness as well as women's struggle to show its existence. Nawal el Sadawi’s Perempuan di Titik Nol is one of them. As an adherent of feminist existentialism, Nawal tries to provide solutions for the improvement of women's existence by: working, learning, becoming agents of change, and tough.